2016
DOI: 10.1109/tvt.2015.2417500
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Adaptive Power Allocation for Incremental MIMO Systems

Abstract: Abstract-We consider energy-efficient adaptive power allocation for three incremental multiple-input multiple-output (IMIMO) systems employing ARQ, hybrid ARQ (HARQ) with Chase combining (CC), and HARQ with incremental redundancy (IR), to minimize their rate-outage probability (or equivalently packet drop rate) under a constraint on average energy consumption per data packet. We first provide the rate-outage probability expressions for the three IMIMO systems, and then propose methods to convert them into a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…They showed that HARQ may significantly outperform finite blocklength for a given set of latency, reliability and bit count values. Energy-efficient adaptive power allocation for three incremental multiple-input-multipleoutput (IMIMO) systems employing ARQ, CC-HARQ and IR-HARQ are considered in [19].…”
Section: A Related Workmentioning
confidence: 99%
“…They showed that HARQ may significantly outperform finite blocklength for a given set of latency, reliability and bit count values. Energy-efficient adaptive power allocation for three incremental multiple-input-multipleoutput (IMIMO) systems employing ARQ, CC-HARQ and IR-HARQ are considered in [19].…”
Section: A Related Workmentioning
confidence: 99%
“…Fig. 3 shows a comparison of CDFs of the exact SINR in (17) and the approximated SINR in (21) the Meijer's-G function [26]. Then, using the inverse Laplace transform, the PDF and CDF ofγ lk,m can be derived as…”
Section: B Harq-ccmentioning
confidence: 99%
“…In [16], the authors also studied the aspects of MIMO-ARQ with nonlinear power amplifier, large-scale MIMO, and adaptive power allocation. The adaptive power allocation to minimize the outage probability of incremental MIMO systems was studied under a constraint on average energy consumption per packet, employing Type-I HARQ, HARQ-CC, and HARQ-IR in [17]. The minimum number of the transmit/receive antennas required to satisfy outage probability constraints were studied for large-but-finite scale MIMO with/without ARQ feedback in [18].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution conducted in [10] evaluated power allocation for HARQ-IR in downlink scenario under the respect of Quality of Service (QoS). In addition EE was described in [11] through power adaptation in various Incremental Multiple Input Multiple Output (IMIMO) scenarios based on ARQ, HARQ-CC, and HARQ-IR where the purpose is to reduce the outage probability. In [12] it has been reported three optimization approaches namely energy per bit reduction, minimizing the normalization between energy per bit and SE, the trade-off between EE and SE.…”
Section: Introductionmentioning
confidence: 99%